Age-Related Decrease in the Mitochondrial Sirtuin Deacetylase Sirt3 Expression Associated with ROS Accumulation in the Auditory Cortex of the Mimetic Aging Rat Model - Zeng, Lingling; Yang, Yang; Hu, Yujuan; Sun, Yu; Du, Zhengde; Xie, Zhen; Zhou, Tao; Kong, Weijia (PLOS ONE, 2014)
Age-related dysfunction of the central auditory system, also known as central presbycusis, can affect speech perception and sound localization. Understanding the pathogenesis of central presbycusis will help to develop novel approaches to prevent or treat this disease. In this study, the mechanisms of central presbycusis were investigated using a mimetic aging rat model induced by chronic injection of D-galactose (D-Gal). We showed that malondialdehyde (MDA) levels were increased and manganese superoxide dismutase (SOD2) activity was reduced in the auditory cortex in natural aging and D-Gal-induced mimetic aging rats. Furthermore, mitochondrial DNA (mtDNA) 4834 bp deletion, abnormal ultrastructure and cell apoptosis in the auditory cortex were also found in natural aging and D-Gal mimetic aging rats. Sirt3, a mitochondrial NAD+-dependent deacetylase, has been shown to play a crucial role in controlling cellular reactive oxygen species (ROS) homeostasis. However, the role of Sirt3 in the pathogenesis of age-related central auditory cortex deterioration is still unclear. Here, we showed that decreased Sirt3 expression might be associated with increased SOD2 acetylation, which negatively regulates SOD2 activity. Oxidative stress accumulation was likely the result of low SOD2 activity and a decline in ROS clearance. Our findings indicate that Sirt3 might play an essential role, via the mediation of SOD2, in central presbycusis and that manipulation of Sirt3 expression might provide a new approach to combat aging and oxidative stress-related diseases.